2002
DOI: 10.1007/s001220100756
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new low-molecular-weight glutenin subunit genes in wheat

Abstract: To clarify the composition of low-molecular-weight glutenin subunits (LMW-GSs) in a soft wheat cultivar, we cloned and characterized LMW-GS genes from a cDNA library and genomic DNA in Norin 61. Based on alignment of the conserved N- and C- terminal domains of the deduced amino-acid sequences, these genes are classified into 12 groups. One of these groups (group 5), the corresponding gene of which has not been reported previously, contains two additional hydrophobic amino-acid clusters interrupting the N-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
3
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 20 publications
0
122
3
1
Order By: Relevance
“…Immature seeds were harvested 7,10,15,20,25,30, and 35 d after onset of pollination directly into liquid nitrogen and stored at 280˚C until use (20). Rye, barley, oat, spelt, and rice grains produced by Alnatura (Bickenbach, Germany) were bought at a local drugstore.…”
Section: Methodsmentioning
confidence: 99%
“…Immature seeds were harvested 7,10,15,20,25,30, and 35 d after onset of pollination directly into liquid nitrogen and stored at 280˚C until use (20). Rye, barley, oat, spelt, and rice grains produced by Alnatura (Bickenbach, Germany) were bought at a local drugstore.…”
Section: Methodsmentioning
confidence: 99%
“…The DNA sequences for the group 3 type II LMW subunits show very strong similarities [20], so the peptide mass maps should be expected to have significant overlap. As a result, the data do not provide definitive evidence that all of the expected subunits are present.…”
Section: Lmw Protein Identitiesmentioning
confidence: 99%
“…The presence of BAB78741 and BAB78742 are perhaps the most definitive, since they both have one predicted peptide not present in the others. For© the© tentatively© identified© LMW© group© 2© type© I subunit© (BAB78738),© three© of© the© six© predicted© peptides were© observed© in© the© MALDI© QqTOF© peptide© pattern (data©not©shown).©A©higher©mass©peptide©was©also identified©at©5426.3©Da,©which©matches©a©predicted peptide© at© 5426.2© Da.© Now,© only© a© few© DNA© sequences for© this© group© have© been© determined© in© contrast© to© the group© 3© subunits© discussed© above© [20].…”
Section: Lmw Protein Identitiesmentioning
confidence: 99%
“…PCR reactions were performed in a total volume of 25 µL containing 1.5 mM MgCl 2 , 0.1 mM of each dNTP, 5 pmol of Glu13 (5'-TTGGGGCTGT-TGTTGCTGATA-3') and Glu22 (5'-CGTCTTTGC-CCTCCTCGCTC-3') primer set 9 and 0.5 U AmpliTaq Gold DNA polymerase (Applied Biosystems Co., Ltd. USA), × 1 PCR Gold buffer and about 50 ng of total DNA. Reactions were performed according to the following protocol: denaturation at 94°C for 3 min; 35 cycles of 94°C for 30 s, 55°C for 30 s, 72°C for 90 s; and a final extension at 72°C for 5 min.…”
Section: Dna Sample Preparation and Pcr Analysismentioning
confidence: 99%
“…Cloned sequences of the LMW-GS genes revealed that all of the predicted LMW-GS amino acid sequences contained 8 cysteine residues 3,4 , which are considered to be involved in the formation of intra-and inter-molecular disulfide bonds. In our previous study, we analyzed the composition of the LMW-GS genes comprehensively in a soft wheat cultivar Norin 61 and classified these genes into 12 groups based on their deduced amino acid sequence similarity 9 . In this study, we analyzed the relationships between the LMW-GS composition and gluten strength (gluten index) using single-seed descent lines derived from the Kitakeiharu 717 (KKS 717) / Grandin cross.…”
Section: Introductionmentioning
confidence: 99%